THE EFFECT OF CHANGES IN TAX RATE AND TAX INCENTIVES ON TAXPAYER COMPLIANCE OF MSMES IN SIANTAR DISTRICT - Hanum, Zulia; Hidayatul Aulia, Adinda (Proceeding International Seminar of Islamic Studies, 2022)
This study aims to determine the effect of changes in tax rates and tax incentives on MSME taxpayer compliance in Siantar District, especially PematangSimalungun. This research uses quantitative research with survey research typebecause the data used in this study are primary data obtained through questionnaires.The sample in this study was caluculated using the slovin formula in order to obtain 72MSME actors who became research respondents. The sampling technique used issimple random sampling technique. Data collection techniques were carried out bydistributing questionnaires to respondents. The data analysis technique used in this study is multiple linear regression analysis with SPSS (Statistical Product ServiceSolution) Version 26 software. The results of this study indicate that changes in taxrates and tax incentives significantly affect MSME taxpayer compliance partially orsimultaneouslu in Siantar District.Keywords: Changes in Tax Rates, Tax Incentive, Taxpayer Compliace, MSMEs_______________________________________________________________________